Involvement of cecropin B in the formation of the Aedes aegypti mosquito cuticle - Liu, Wei-Ting; Tu, Wu-Chun; Lin, Chao-Hsiung; Yang, Ueng-Cheng; Chen, Cheng-Chen (Scientific reports, 2017)
In this study, we found a mosquito antimicrobial peptide (AMP), Aedes aegypti cecropin B (Aacec B), was expressed constitutively in pupae. Knockdown in the pupae of Aacec B using double-stranded RNA (dsRNA) resulted in high mortality, the emergence of deformed adults and an impairment of pharate adult cuticle formation with fewer lamellae being deposited and the helicoidal pattern of the chitin microfibrils being disorganized. Simultaneous injection of Aacec B dsRNA and Aacec B peptide into pupae significantly reduced this mortality and no deformed adults then emerged. The expression levels of Ae. aegypti prophenoloxidase (AaPPO) 3 and AaPPO 4 were significantly reduced in the Aacec B knockdown pupae. Exogenous Aacec B peptide significantly enhanced the transcription of AaPPO 3 in pupae. Knockdown of AaPPO 3 in pupae caused effects similar to Aacec B-knockdown. The Aacec B peptide could be detected in both the cytoplasm and nuclei of pupal cells and was able to bind to the TTGG(A/C)A motif in AaPPO 3 DNA both in vitro and in vivo . These findings suggest that Aacec B plays a crucial role in pharate adult cuticle formation via the regulation of AaPPO 3 gene expression in pupae.